Integrated store concept in Singapore - Chan, Diana Jie Mei (2008)
This paper primarily seeks to explore the feasibility of an integrated store concept in Singapore. As a preamble to our discussion integrated store concept, we would first be examining and thus, summarizing the key success factors of both the Personal Goods Retail Industry (PGRI) and Food & Beverage Retail Industry (FBRI) in Singapore by looking at various case studies of non-integrated retail stores. The integration of the key success factors will then contribute to the success of the integrated store concept. The next section will be an analysis of the Singaporean consumer in terms of their lifestyle demands and needs, for the purpose of examining the potential market for an integrated store. Following that would be the proposed strategies for targeting consumer segments who would patronize an integrated store.